Tribological Study Of Additive Manufactured Aluminium Alloy ER5356 For Potential Part Repair - Mohd Noor Ariffin, Siti Syairah (Universiti Sains Malaysia, 2022)
Aluminum alloys are widely used in a range of automotive parts due to their high strength-to-weight ratio. Unfortunately, it’s resistance to wear is relatively low, result in short part life upon application due to sliding contact. As an alternative unfitted part due to severe worn which is currently send to landfill, has second chance to service via reconstruction of the worn area using metal additive manufacturing method. However, the properties of deposited material need to be studied before it fit to be reused. The study intent to investigate the performance of additive manufactured aluminium alloy on tribology properties like wear rate (mm3 /Nm) and coefficient of friction. This experiment considers cold forging and unforging specimen ER5356 utilising a reciprocating ball-on-flat arrangement with a speed of 30RPM, 50RPM and 70RPM with different load of 1KG, 3KG and 5KG. The result found that the welded specimen of cold forging indicated lower value of coefficient of friction (COF) and wear rate (mm3 /Nm). For the hardness of cold forging samples shows that the highest value compared to others condition. The results of the experiment are compared and it has been observed good agreement. Based on the initial findings, the additive manufactured material result in less wear rate (mm3/Nm) compared to material that non-weld, but for the coefficient of friction is almost same.